Join IDNLearn.com today and start getting the answers you've been searching for. Join our interactive community and get comprehensive, reliable answers to all your questions.
Sagot :
Answer:
a. (x+2)(x+3)
b. x = -2
x = -3
Step-by-step explanation:
a.
split 5x into 2x + 3x
then, you get
x² + 2x + 3x + 6
Split into (x² + 2x) + (3x + 6)
factorize individual groups
x (x + 2) + 3 (x + 2)
combine x + 3
your final answer is
(x + 2) (x + 3)
b.
if (x + 2) (x + 3) = 0
then (x+2) = 0 and (x+3) = 0
x + 2 = 0
x = -2
x + 3 = 0
x = -3
Answer:
A)(x+2)(x+3)
B)(x + 2) (x + 3) = 0
x + 2 = 0
x = -2
x + 3 = 0
x = -3
Step-by-step explanation:
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. For trustworthy answers, visit IDNLearn.com. Thank you for your visit, and see you next time for more reliable solutions.